Perbedaan Efektivitas Zeolit dan Manganese Greensand untuk Menurunkan Kadar Fosfat dan Chemical Oxygen Demand Limbah Cair “Laundry Zone” di Tembalang - Dahona Lenthe Lavina; Sulistyani Sulistyani; Mursid Rahadjo (Jurnal Kesehatan Masyarakat (Undip), 2016)
Laundry business is a business in clothes washing services. Preliminary test results show that the levels of phosphate and COD laundry liquid wastes is 12,36 mg/l and 5.920 mg/l. These levels exceeded the water quality standard of waste that phosphate concentration of 2 mg/l and COD concentration of 100 mg/l. This research aimed to determine the difference effectiveness of zeolite and manganese greensand to decrease phosphate and chemical oxygen demand on waste  "laundry zone" in Tembalang. This research uses Quasi-Experimental with pretest - posttest design. The sample used is wastewater from the washing machine outlet of "laundry Zone". Analysis data used to test hypothesis is by one way anova test with 95% significance level. Research result show  that phosphate levels before treatment is 12,36 mg/l and COD levels is 5.920 mg/l. After treatment with zeolite and manganese greensand in diameter 0,25 mm, 0,5 mm, 0,75 mm and 1 mm showed that the levels of phosphate and COD decreased. From one way anova got the difference at significant of α = 0,05  decreased levels of phosphate and COD after media zeolite by p-value = 0,001, the difference at significant of α = 0,05 decreased levels of phosphate and COD after media manganese greensand by p-value = 0,01, and the difference at significant of α = 0,05 decreased levels of phosphate and COD after media zeolit and manganese greensand by p-value = 0,0001. Effectiveness of the highest decline in phosphate and COD reached 73,30 % dan 71,68% occurred in treatment with zeolite diameter of 0,25 mm.